Improving phosphorus sustainability of sugarcane production in Brazil - Soltangheisi, Amin (2019)
Phosphorus (P) use in global food and bioenergy production needs to become more efficient and sustainable to reduce environmental impacts and conserve a finite and critical resource (Carpenter & Bennett, Environmental Research Letters, 2011, 6, 014009; Springmann et al., Nature, 2018, 562, 519). Sugarcane is one crop with a large P footprint because production is centered on P-fixing soils with low P availability (Roy et al., Nature Plants, 2016, 2, 16043; Withers et al., Scientific Reports, 2018, 8, 2537). As global demand for processed sugar and bioethanol continues to increase, we advocate that improving P efficiency could become a key sustainability goal for the sugarcane industry. Here, we applied the 5R global P stewardship framework (Withers et al., Ambio, 2015, 44, 193) to identify more sustainable options to manage P in Brazilian sugarcane production. We show that current inputs of P fertilizer to the current crop area could be reduced by over 305 Gg, or 63%, over the next three decades by reducing unnecessary P fertilizer use, better utilization of recyclable bioresources and redesigning recommendation systems. Adoption of these 5R options would save the sugarcane industry in Brazil 528 US$ million and help safeguard global food and energy security.